Pharmacological treatment of high‐normal blood pressure (prehypertension) in high‐risk patients for primary prevention of cardiovascular events. Issue 9 (20th August 2020) - Borazjani, Roham; Kojuri, Javad; Abdi‐Ardekani, Alireza; Izadpanah, Peyman; Dehghani, Pooyan; Sayadi, Mehrab; Attar, Armin
Abstract: Currently, the best treatment strategy for patients with a high‐normal blood pressure (prehypertension) is not known. The authors aimed to determine whether pharmacological reduction of systolic blood pressure (SBP) to a normal level (<120 mm Hg) would prevent cardiac morbidity and mortality in prehypertensive patients. In this secondary analysis, the authors obtained the data from SPRINT from the National Heart, Lung, and Blood Institute data repository center. Among 9361 patients enrolled in SPRINT, 289 high‐risk (ASCVD risk = 24.8% ± 13.0 [10‐65]) prehypertensive patients without previous cardiovascular disease and not receiving any antihypertensive medications were enrolled. One hundred and forty‐eight of them were assigned to standard treatment which consisted of clinical follow‐up till SBP goes above 140 mm Hg and then staring medications to keep SBP <140 mm Hg. One hundred and forty‐one were assigned to the intensive treatment receiving pharmacological SBP reduction to <120 mm Hg upon enrollment. The primary composite outcome was myocardial infarction, and other acute coronary syndromes, stroke, heart failure, or death from cardiovascular causes. Throughout the 3.06 years of follow‐up, a primary outcome event was confirmed in three participants (0.74% per year) in the intensive‐treatment group and 8 (1.61% per year) in the standard‐treatment group (hazard ratio [HR], 0.19; P = .045). Rates of serious adverse events were not increased by intensive‐treatment (HR, 0.83; P = .506). Based on this secondary post hoc analysis, intensive SBP reduction may probably be beneficial for primary prevention of cardiovascular morbidity and mortality in high‐risk prehypertensive patients. This finding needs to be evaluated in a larger trial designed specifically to answer this question.